Narrow-band Bandpass Filters with Improved Upper Stopband Using Open/Shorted Coupled Lines - Feng, Wenjie; Hong, Meiling; Che, Wenquan (Applied Computational Electromagnetics Society Journal (ACES), 2021)
Two transversal narrow-band bandpass filters with improved stopband based on open/shorted coupled lines and transversal signal-interaction concepts are proposed in this paper. By utilizing the stopband transmission characteristic of the open/shorted coupled lines, three transmission zeros can be easily achieved to suppress the second harmonic for the first bandpass filter. To further reduce the circuit size of the first filter, unequal open stubs and transmission lines are used for the second bandpass filter with six transmission zeros in the upper stopband. The transmission zeros near the passband can be adjusted conveniently by only changing the electrical length of the open/shorted stubs when the ratio of characteristic impedance is fixed. To verify the presented concepts, two prototypes (?r =2.65, h = 0.508 mm, tan? = 0.003) with 3-dB fractional bandwidths (FBWs) of 4.3% (1.78-1.86 GHz), 2.8% (1.76-1.81 GHz) are designed and fabricated. Good agreements are observed for the theoretical and measured results, indicating good in-band filtering performances and high selectivity.